Design and Performance Testing of Mini Capstan Lathe Machine - Muhammad Akmal Abdul Karim; Tengku Nur Azila Raja Mamat (Progress in Engineering Application and Technology, 2022)
Technology has advanced and continues to improve since the dawn of time, particularly lathes. This technology is critical to the seamless manufacture of items in the industry. Without this technology, the industry’s output would be sluggish, and the quality will most likely be poor. Today’s advancements in lathe technology will assist in resolving this issue by making it easier for consumers to make high-quality items. A lathe is a machine that turns a workpiece to execute operations such as cutting, drilling, assembling, and rotating. The Capstan and Turret Lathe is one of the most often utilised lathes in the industry. After each tower action is turned, these machines use a hexagonal turret head instead of a tailstock to conduct numerous operations successively without changing tools manually. The project shows how the design was created and how it was implemented. A tiny lathe is driven by an electric motor in this machine. The surface smoothness of the product generated by this machine will be tested to confirm that it is of the same quality as the product produced by the existing lathe machine.